Robotic thoracic surgery: The state of the art - Kumar, Arvind (J Minim Access Surg, 2015)
Minimally invasive thoracic surgery has come a long way. It has rapidly progressed to complex procedures such as lobectomy, pneumonectomy, esophagectomy, and resection of mediastinal tumors. Video-assisted thoracic surgery (VATS) offered perceptible benefits over thoracotomy in terms of less postoperative pain and narcotic utilization, shorter ICU and hospital stay, decreased incidence of postoperative complications combined with quicker return to work, and better cosmesis. However, despite its obvious advantages, the General Thoracic Surgical Community has been relatively slow in adapting VATS more widely. The introduction of da Vinci surgical system has helped overcome certain inherent limitations of VATS such as two-dimensional (2D) vision and counter intuitive movement using long rigid instruments allowing thoracic surgeons to perform a plethora of minimally invasive thoracic procedures more efficiently. Although the cumulative experience worldwide is still limited and evolving, Robotic Thoracic Surgery is an evolution over VATS. There is however a lot of concern among established high-volume VATS centers regarding the superiority of the robotic technique. We have over 7 years experience and believe that any new technology designed to make minimal invasive surgery easier and more comfortable for the surgeon is most likely to have better and safer outcomes in the long run. Our only concern is its cost effectiveness and we believe that if the cost factor is removed more and more surgeons will use the technology and it will increase the spectrum and the reach of minimally invasive thoracic surgery. This article reviews worldwide experience with robotic thoracic surgery and addresses the potential benefits and limitations of using the robotic platform for the performance of thoracic surgical procedures.